2021
DOI: 10.3390/ma14051277
|View full text |Cite
|
Sign up to set email alerts
|

PDMAEMA/Polyester Miktopolymers: Synthesis via In-Out Approach, Physicochemical Characterization and Enzymatic Degradation

Abstract: Synthesis, physicochemical characterization, and the enzymatic degradation of the amphiphilic miktoarm star-shaped polymers is reported herein. First, star-shaped macroinitiators, based on N,N′-dimethylaminoethyl methacrylate (DMAEMA) and glycerol dimethacrylate (GDMA) ((PDMAEMA)n-PGDMA), were synthesized. Due to the presence of hydroxyl groups in the macroinitiator core, polyesters such as poly(ɛ-caprolactone) (P(ɛ-CL)), polylactide (PLA) and poly(lactide-co-glycolide) (PLGA) were synthesized using ring openi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In our previous works concerning the degradation of PDMAEMA/polyester block copolymers, we have shown that enzymatic degradation using Novozyme 435 primarily involved the ester bonds in PDMAEMA side chains, and the rate of polyester degradation decreased with the increase in the chain length of PDMAEMA [ 24 ]. Whereas in the case of PDMAEMA/polyester miktoarm stars obtained via an in–out approach, enzymatic degradation performed using lipase from Pseudomonas cepacia showed an increased degradation rate for the polymer with PCL arms [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous works concerning the degradation of PDMAEMA/polyester block copolymers, we have shown that enzymatic degradation using Novozyme 435 primarily involved the ester bonds in PDMAEMA side chains, and the rate of polyester degradation decreased with the increase in the chain length of PDMAEMA [ 24 ]. Whereas in the case of PDMAEMA/polyester miktoarm stars obtained via an in–out approach, enzymatic degradation performed using lipase from Pseudomonas cepacia showed an increased degradation rate for the polymer with PCL arms [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research was focused on the synthesis of miktoarm star-shaped polymers via a coupling-onto [ 26 ] or in–out method [ 25 ]. In this study, a series of well-defined miktoarm star-shaped copolymers based on DMAEMA and cyclic esters were obtained by facile one-pot synthesis using a combination of techniques such as ATRP, ROP, and click reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies involved comprehensive degradation studies on enzymatic degradation using lipase from Pseudomonas cepacia [24]. Herein, we performed a degradation study of PCL-b-PDMAEMA, PLA-b-PDMAEMA and PLGC-b-PDMAEMA copolymers under simulated physiological conditions, namely, hydrolytic degradation in PBS at different pHs, and enzymatic degradation using Novozyme 435.…”
Section: Introductionmentioning
confidence: 99%
“…Because PDMAEMA usage is limited by the lack of biodegradability in vivo model (143), since PDMAEMA has an immune suppressive effect, if not degradable, it might cause immunosuppression and increase the risk of infection or tumorigenesis. Previous studies have reported that PLGA is a biocompatible and biodegradable polymer (144).…”
Section: Chapter VI Discussionmentioning
confidence: 99%